One-Pot Synthesis of W-TiO2/SiO2 Catalysts for the Photodegradation of p-Nitrophenol. (1st August 2019) - Sánchez, Ulises Arellano; Chen, Lifang; Wang, Jin An; Noreña, Luis Enrique; Asomoza, Maximiliano; Solis, Silvia; Zhou, Xiaolong; Song, Yueqin; Liu, Jing
Abstract : Double modifications of TiO2 by doping with WO3 and by dispersing on a SiO2 support were made by the one-pot sol-gel method. Doping with W shifts the TiO2 band gap energy from 3.2 eV to around 3.06 eV. The surface area of the supported W-TiO2 /SiO2 material was significantly increased, by approximately 3 times, in comparison to the bare TiO2 . The photocatalytic activities of the catalysts were evaluated in the degradation reaction of p -nitrophenol in aqueous solution and basic medium. After 240 min of photodegradation, more than approximately 99% p -nitrophenol could be mineralized with the most active W-TiO2 /SiO2 catalyst. Under UV irradiation, p -nitrophenol was initially photodegraded into hydroquinone and benzosemiquinone intermediates, which were further degraded into smaller fragments such as organic carboxylic acids and finally completely mineralized. A proposed photoreaction mechanism was presented based on the key roles of the surface hydroxyl species and superoxide radicals such as O2 - and ⋅ OH, together with W 6+ /W 5+ couples and e - /h + pairs in the catalysts in the p -nitrophenol photodegradation. The one-pot sol-gel synthesis method was proven to be effective to obtain W-TiO2 /SiO2 catalyst with large surface area and high photocatalytic activity, and it can be also used for the preparation of other heterogeneous catalysts.